Ferroptosis induces membrane blebbing in placental trophoblasts - Kajiwara, Kazuhiro (2022)
Ferroptosis is a regulated, non-apoptotic form of cell death, characterized by hydroxy-peroxidation of discrete phospholipid hydroperoxides, particularly hydroperoxyl (Hp) forms of arachidonoyl- and adrenoyl-phosphatidylethanolamine, with a downstream cascade of oxidative damage to membrane lipids, proteins and DNA, culminating in cell death. We recently showed that human trophoblasts are particularly sensitive to ferroptosis caused by depletion or inhibition of glutathione peroxidase 4 (GPX4) or the lipase PLA2G6. Here, we show that trophoblastic ferroptosis is accompanied by a dramatic change in the trophoblast plasma membrane, with macro-blebbing and vesiculation. Immunofluorescence revealed that ferroptotic cell-derived blebs stained positive for F-actin, but negative for cytoplasmic organelle markers. Transfer of conditioned medium that contained detached macrovesicles or co-culture of wild-type target cells with blebbing cells did not stimulate ferroptosis in target cells. Molecular modeling showed that the presence of Hp-phosphatidylethanolamine in the cell membrane promoted its cell ability to be stretched. Together, our data establish that membrane macro-blebbing is characteristic of trophoblast ferroptosis and can serve as a useful marker of this process. Whether or not these blebs are physiologically functional remains to be established.